2008
DOI: 10.1097/rlu.0b013e31818bf36d
|View full text |Cite
|
Sign up to set email alerts
|

Para-Hyoid Ectopic Parathyroid Adenoma Localized by Tc-99m MIBI SPECT

Abstract: A 64-year-old woman with a history of I-131 ablation for Graves hyperthyroidism and bilateral parathyroid exploration with resection of a left inferior parathyroid adenoma presented 2 years after surgery with marked fatigue, irritability, and joint pain. Laboratory testing revealed an elevated calcium and parathyroid hormone levels suspicious for hyperparathyroidism. The ultrasound indicated no evidence of a parathyroid adenoma. Tc-99m-MIBI SPECT demonstrated a focus of uptake posteroinferior to the right subm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
1
0
0
Order By: Relevance
“…Roy et al found that ectopic parathyroid glands were predominantly located in the thymus (38%), followed by the retroesophageal region (31%) and then the intrathyroidal region (18%) [28]. In the present study, the ectopic nodules occurred in the suprasternal fossa (81.8%), inside the thyroid (4.5%), the mandibular area (9.1%) [34] and outside of the left carotid artery (4.5%). Eighteen patients presented with a single ectopic nodule (90%) and two patients presented with two nodules (10%), which were consistent with a prior report [28].…”
Section: Discussionsupporting
confidence: 47%
“…Roy et al found that ectopic parathyroid glands were predominantly located in the thymus (38%), followed by the retroesophageal region (31%) and then the intrathyroidal region (18%) [28]. In the present study, the ectopic nodules occurred in the suprasternal fossa (81.8%), inside the thyroid (4.5%), the mandibular area (9.1%) [34] and outside of the left carotid artery (4.5%). Eighteen patients presented with a single ectopic nodule (90%) and two patients presented with two nodules (10%), which were consistent with a prior report [28].…”
Section: Discussionsupporting
confidence: 47%